PENINGKATAN HASIL BELAJAR LAY UP BOLABASKET MELALUI PENDEKATAN BERMAIN ONE-TWO STEP PADA SISWA KELAS VIII SMP NEGERI 9 SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve student learning outcomes in the following study lay up basketball in the eighth C grade students of SMP N 1 Semarang in 2013 through the medium of the game one-two step.This research is a class act. This study used 2 cycles, where each cycle consists of: 1) planning, 2) implementation of the action; 3) observation; 4) reflection. Research conducted includes three domains, namely the domain of psychomotor, affective, cognitive domain.The results showed that the learning outcomes lay up basketball game with the media one-two step in class VIII C 9 Semarang SMP N positive impact, as seen in the results of students' mastery learning which exceeds a predetermined KKM has increased by 75 in the first cycle in the form of completeness study reached 50%, while in the second cycle reached 88.46% mastery learning. It is concluded that learning the lay-up basketball game with the use of media one-two-step has a positive effect, which can improve student learning outcomes that can facilitate students to understand and perform langkahan lay up correctly.